Effect of the Features of Functionalized Structure on Elastic Properties and Strength of Partially-Filled Brittle Porous Materials; AIP Conference Proceedings; Vol. 1783 : Advanced Materials with Hierarchical Structure for New Technologies and Reliable Structures 2016 - Konovalenko I. S. Igor Sergeevich; Shilko E. V. Evgeny Viktorovich; Konovalenko I. S. Ivan Sergeevich; Vodopjyanov E. M. Egor (2016, 2016)
Title screen